EDUCATIONAL OPPORTUNITIES OF THE USE OF CASE-STUDY TECHNOLOGY IN TEACHING PRIMARY SCHOOL STUDENTS - Abdullayeva Diloromxon Numonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is devoted to the educational capabilities of modern case-study Technology in improving the quality efficiency of primary education.